Load-Frequency Control of a Hybrid Islanded Microgrid with a Fractional Order Fuzzy PID Controller Optimized by Cheetah Algorithm - Siavash Shirali; Saeed Zolfaghari Moghaddam; Mortaza Ali Asghary (مجله مدل سازی در مهندسی)
Hybrid microgrid is a new concept that has been introduced in recent decades based on the needs of power systems. One of the most important challenges of the islanded microgrid is frequency regulation. In this paper, a fractional order fuzzy PID controller is introduced to stabilize the frequency. The presence of a fractional order in the controller system improves the stability and response speed of the controller in different conditions. Determining the controller coefficients is an important challenge that can be done using different methods. This paper uses Cheetah optimization algorithm because of its important features such as: preventing premature convergence and not getting stuck in the local optimum, which differentiates it from other algorithms. It should be noted that the structure of the proposed controller is a centralized control type, in which the control signal is sent to the units of energy storage sources and diesel generator. For more accurate modeling of energy storage resources, limiting blocks are included in the output of these resources. To evaluate the performance of the proposed controller, its results have been compared with other controllers, namely: classic PID, fractional order PID and fuzzy PID controllers optimized with other optimization algorithms such as PSO, SCA and GA, using several criteria including: IAE, ISE, ITAE and ITSE. The results show that the proposed controller has the lowest error in terms of error measurement criteria and the highest speed of convergence, with optimal and acceptable performance relative to other controllers are mentioned..